2014
DOI: 10.1186/s12879-014-0602-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of tuberculosis in Sicily, Italy: what has changed after a decade?

Abstract: BackgroundWe aimed to investigate the molecular epidemiology of Mycobacterium tuberculosis complex (MTBC) isolates in the province of Palermo, Sicily, Italy, by characterizing 183 isolates identified in the years 2004-2012. A comparison with 104 MTBC strains identified in the same geographic area in the years 1994-2000 was also carried out.MethodsOne hundred eighty-three MTBC isolates identified in Palermo, Italy, in the years 2004-2012 were analyzed by spoligotyping and the 24 mycobacterial interspersed repet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Other studies have reported an association between previous history of TB treatment and anti-TB-drug resistance 48,49. In addition, a study in Palermo, Italy reported a wide heterogeneity among the MTB strains observed, which illustrates rapid changes in TB epidemiology 50. This indicates the existence of ongoing transmission of DR strains, and could indicate weakness in TB prevention and control measures, as it is convoyed by resistance to rifampicin in new cases as well.…”
Section: Discussionmentioning
confidence: 93%
“…Other studies have reported an association between previous history of TB treatment and anti-TB-drug resistance 48,49. In addition, a study in Palermo, Italy reported a wide heterogeneity among the MTB strains observed, which illustrates rapid changes in TB epidemiology 50. This indicates the existence of ongoing transmission of DR strains, and could indicate weakness in TB prevention and control measures, as it is convoyed by resistance to rifampicin in new cases as well.…”
Section: Discussionmentioning
confidence: 93%
“…In Sicily, an average of 4.4 human cases/100,000 inhabitants was reported until 2013, and the proportion of cases was higher in foreign‐born individuals (Mammina et al., ). A genetic study on MTBC isolates from native and foreign population in the province of Palermo showed a wide genetic heterogeneity of the isolates and four M. bovis strains (3.7%) was identified only from Sicilian‐born patients (Bonura et al., ). The province of Palermo together with Messina and Enna is the ones with the highest prevalence of bTB in cattle so it is possible that human cases are also present.…”
Section: Discussionmentioning
confidence: 99%
“…The standard 24 MIRU-VNTR loci method [ 18 ] was performed based on agarose gel electrophoresis. The simplex PCR product size was determined as previously reported [ 43 ].…”
Section: Methodsmentioning
confidence: 99%